Comparative susceptibility of Glossina longipennis and G. brevipalpis to pathogenic species of Trypanosoma - Moloo, S.K.; Okumu, I.O.; Kuria, N.M. (Wiley, 1998)
The susceptibility of G. longipennis, G. brevipalpis and G. morsitans centralis to various strains of Trypanosoma vivax, T. congolense and T. brucei brucei was investigated in the laboratory. Cattle and goats were infected with the trypanosomes and the tsetse fed from them during the first parasitaemic wave. Thereafter the flies were maintained on rabbits and were dissected on day 25 for T. vivax and T. congolense or day 30 for T. b. brucei, and the midgut, labrum, hypopharynx and salivary glands examined for trypanosomes. It was shown that the laboratory-reared G. longipennis and G. brevipalpis had differing susceptibilities to the trypanosome species used, being highly susceptible to T. vivax, less susceptible to T. congolense, and T. b. brucei could not infect their salivary glands, although G. m. centralis became infected with all Trypanosoma spp.